PERAN PETUGAS TATA USAHA DALAM MENJAGA KUALITAS MANAJEMEN PERSURATAN DI SMP MUHAMMADIYAH 57 MEDAN - Tuffahati, Jihan; Hadi, Firman; Isnaini, Isnaini; Ariesky, Rani Zaskia; Darmansah, Tengku (Cendekia Madani Nusantara, 2024)
This article discusses the role of administrative officers in maintaining the quality of correspondence management at SMP Muhammadiyah 57 Medan. Effective and efficient correspondence management is an important aspect in school operations, because correspondence functions as an official communication tool that documents various activities and decisions. This research uses a qualitative approach with a case study method, where data is collected through in-depth interviews with administrative officers, direct observation and document analysis. The research results show that administrative officers at SMP Muhammadiyah 57 Medan have a very vital role in managing the entire correspondence process, starting from receiving, recording, storing, to distributing letters. They are responsible for ensuring that every incoming and outgoing letter is managed well, according to established procedures, and neatly documented. Good quality of correspondence management is reflected in accuracy, timeliness and regularity in document archiving. Administrative officers also play a role in maintaining the confidentiality of information, preventing loss or damage to documents, and ensuring that important documents are available when needed. The implementation of information technology in correspondence management also supports the efficiency and effectiveness of their work, although there are still challenges in terms of training and adaptation to new systems. In conclusion, administrative officers play a key role in maintaining the quality of correspondence management at SMP Muhammadiyah 57 Medan. They ensure that the correspondence process runs smoothly and supports overall school operational activities. Therefore, increasing the competency of administrative officers and using appropriate technology is very necessary to continue to improve the quality of correspondence management in this educational institution.